Business model of the enterprise as a tool of building interorganizational relationships = Model biznesowy przedsiębiorstwa, jako narzędzie budowania relacji międzyorganizacyjnych - Danielak, Wiesław (Zielona Góra: Faculty of Economics and Management Press)
The deliberations included in the article concentrate on the essence of the business model of the enterprise as a tool of building interorganizational relationships. The importance of interorganizational relationships has been indicated, the ones, which stay in a close connection with the business model whose elements are people (employees, owners, suppliers, customers) as well as structures, processes and relationships the enterprise establishes with the environment. The elaboration defines the notion of a business model, presents the components of relational exchange between a purchaser and supplier as well as characterizes the elements of interorganizational relationships model.
Keywords: model biznesowy; wymiana relacyjna; relacje międzyorganizacyjne; business model; relational exchange; interorganizational relationships